Understanding disease-specific and non-specific factors predicting disordered eating in adults with coeliac disease. (1st January 2022) - Fraser, Carley N.; Möller, Stephan P.; Knowles, Simon R.
Abstract: An adverse relationship between coeliac disease and the development of disordered eating patterns is well established. The aim of this study was to replicate and extend Satherley et al.'s (2016) study exploring coeliac-specific and non-specific factors predicting disordered eating. An online survey was completed by 187 adults with coeliac disease (90.4% female; Mean age = 48.92; Mean years living with coeliac disease = 11.86). Results indicated that greater disordered eating correlated with being female, poorer dietary adherence, greater gastrointestinal and psychological symptoms, and more coeliac-related food concerns. Hierarchical regression analyses found that psychological distress remained the only predictor of disordered eating when both coeliac-specific and non-specific factors were considered. Age, body mass index, psychological distress, years with coeliac disease and dietary nonadherence were found to significantly predict binge eating severity. The findings suggest that psychological distress is a risk factor for disordered eating in coeliac disease and that binge eating behaviours may be a particularly relevant factor for dietary nonadherence in those living with coeliac disease.